Load-Bearing Capacity of an Oxisol under Burned and Mechanized Harvest Sugarcane Crops - Silva Araújo, Fernando; Menezes de Souza, Zigomar; Soares Souza, Gustavo; Barboza da Silva, Reginaldo [UNESP]; Aguilera Esteban, Diego Alexander; Moraes Tavares, Rose Luiza (MDPI, 2023)
The change in land use and the expansion of mechanized sugarcane production systems have led to an increase in soil compaction levels. Preconsolidation pressure may be used as a useful measure for soil mechanical state, management, and planning of mechanization systems. This study aimed to assess the soil compressive behavior, soil physical properties, and spatial variability of preconsolidation pressure of an Oxisol in sugarcane fields under burned harvest and mechanized harvest and the effects of land use change. The physical soil attributes (granulometry, soil water content, bulk density, total porosity, and macro and microporosity) and preconsolidation pressure were evaluated at 0.00–0.10-m, 0.10–0.20-m, and 0.20–0.30-m layers. The soil load-bearing capacity models were constructed from σp values for soil water contents. We mapped the assessed soil attributes from crossing points in a sampling mesh with regular 10 m intervals in each area and evaluated them via geostatistics. Land-use change towards sugarcane production systems promoted soil compaction. The mechanized harvesting system increased the soil load-bearing capacity in the water range corresponding to the friability region in subsurface layers. The preconsolidation pressure and soil water content exhibited spatial dependence in the sugarcane areas, regardless of the management system employed in the harvesting operations.
Keywords: geostatistics; preconsolidation pressure; Saccharum officinarum; soil compaction; spatial variability